An Investigation into Antecedents of Customer Satisfaction and Loyalty with Reference to Online Purchasing Behavior (Journal of Informatics Education and Research, 2024)
Customer satisfaction and loyalty in the context of online purchasing behavior are influenced by various antecedents, which encompass a wide array of factors ranging from website usability to post-purchase services. Understanding these antecedents is crucial for businesses aiming to thrive in the competitive landscape of e-commerce. The primary antecedents of customer satisfaction in online shopping are website usability. Factors such as intuitive interface design, clear navigation menus, and efficient search functionalities contribute to a positive user experience, leading to higher levels of satisfaction. The study concluded that action and loyalty in online purchasing behavior are influenced by a myriad of antecedents, including website usability, product information, security, and customer service quality, delivery services, perceived value, trust, personalized experiences, and loyalty programs. By understanding and addressing these antecedents effectively, businesses can enhance the overall shopping experience, cultivate loyalty, and drive sustainable growth in the dynamic landscape of e-commerce.